2013
DOI: 10.1016/j.conbuildmat.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Durability of expanded polystyrene mortars

Abstract: The influence of the addition of various types and various concentrations of expanded polystyrene foam (both commercial and recycled) on the durability of Portland cement mortars is studied. In particular, the microstructure is studied utilizing the following methods: Capillary absorption of water, mercury intrusion porosimetry, impedance spectroscopy and open porosity. In addition, the effects of heat cycles and freeze-thaw cycles on compressive strength are examined. Scanning electron microscopy is used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 16 publications
0
49
0
6
Order By: Relevance
“…Preparation of mortars with no additives or one additive failed to achieve the desired physical, mechanical and durability properties (35,36). The software NEMRODW (53) was used to build and analyse the D-optimal design to determine the optimal composition of mortars containing ground and powdered EPS used in the current study.…”
Section: Preparations Of Mortarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of mortars with no additives or one additive failed to achieve the desired physical, mechanical and durability properties (35,36). The software NEMRODW (53) was used to build and analyse the D-optimal design to determine the optimal composition of mortars containing ground and powdered EPS used in the current study.…”
Section: Preparations Of Mortarsmentioning
confidence: 99%
“…EPS beads have been used to design thermally insulating composites made with foamed cement pastes, using additives to prevent segregation and improve adherence (33). However, only a limited amount of research has investigated commercial EPS (34) or various types of waste EPS (35,36) in cement mortars. More recent work reported the properties of cement mortars where Portland cement (CEM I) was replaced by cements with lower clinker (CEM II and CEM III) (37).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the consistency of the concrete containing higher than 60% SPS (e.g., 100% SPS) started to decrease. As mentioned before, for economic reasons a superplasticiser has not been used in the present work, otherwise, it could have improved the consistency [3,8,18,19]. It is worth mentioning that due to the effect of gravity, lightweight concrete usually does not show as much slump as normal-weight concrete with the same consistency [20][21][22][23].…”
Section: Effect Of Spsmentioning
confidence: 99%
“…They also found that the water absorption decreases with increasing the amount of EPS in the mixture. [4] and Ferrandiz-Mas et al [5] highlighted that EPS improves the durability of the concrete. In the present study, two cement-based materials were designed: a lightweight mortar, prepared by mixing EPS beads with cement, and a reference cement paste made with only the same cement.…”
Section: Introductionmentioning
confidence: 99%